Negative Appendicectomies in Young Female Patients with High Clinical Suspicion of Acute Appendicitis - Naeem, Umer; Muhammad Waseem Anwar; Fatima Farooq; Farani, Tariq Mukhtar; Muhammad Danial Yousaf; Muhammad Saqlain (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine negative appendicectomies, both open and laparoscopic, in young female patients with high clinical suspicion of acute appendicitis (Alvarado Score ≥7). Study Design: Quasi-experimental study Place and Duration of Study: Department of General Surgery, Combined Military Hospitals, Rawalpindi and Quetta Pakistan, from Oct 2021 to Nov 2023. Methodology: A total of 150 female patients aged between 12 to 30 years, with Alvarado score ≥7 were included in the study. Baseline characteristics were documented. All patients underwent appendicectomy and retrieved appendix was sent to histopathology lab for histopathological diagnosis based on which negative appendicectomies were identified. Results: In this study, mean age of patients was 21.50±3.16 years. Twenty-eight (18.67%) patients underwent open appendicectomy while 122(81.33%) patients underwent laparoscopic appendicectomy. Composite negative appendicectomy was seen in 37(24.67%) cases. No statistically significant association was found between type of surgery and negative appendicectomy (p=0.595). Conclusion: In young females, even in the presence of high clinical suspicion, the rate of negative appendicectomies is relatively high.